Optimizing the Understanding of Accounting and Tax Obligations in Palm Oil Plantation Cooperatives: An Institutional Theory and Deterrence Theory Perspective - Josua Alister; Yulianti Abbas (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
Understanding Accounting and Tax Obligations is a crucial aspect for palm oil plantation partnership cooperatives in maintaining financial health and regulatory compliance. This study examines cooperative managers’ understanding of accounting and tax obligations and recommends optimization strategies that can be implemented both internally and externally. The research adopts a qualitative approach through in-depth interviews with four cooperatives in East Kalimantan, the core companies, the Cooperative Office, and the Tax Office. The novelty of this research lies in its discussion of accounting comprehension followed by tax understanding within palm oil plantation cooperatives. The findings indicate that while cooperatives are aware of their obligations, their implementation remains materially inadequate, influenced by external pressures and sanctions. Proposed strategies include, internally, the recruitment of experts by cooperatives and improvement of plantation recordkeeping governance. Externally, collaboration between the Cooperative Office and the Tax Office in providing assistance is necessary, as well as the establishment of communication channels among core companies, cooperatives, and the tax office for ongoing support. As a final step, tax audits by the authorities can be conducted to further enhance understanding. Keywords: Cooperative; Oil Palm; Accounting; Tax Liability;